Out there screaming eaudiobook An anthology of new black horror. - Peele, Jordan (Books on Tape, 2023)
NEW YORK TIMES BESTSELLER • The visionary writer and director of Get Out , Us , and Nope , and founder of Monkeypaw Productions, curates this groundbreaking anthology of all-new stories of Black horror, exploring not only the terrors of the supernatural but the chilling reality of injustice that haunts our nation. “Every piece is strong and memorable, making this not only likely to be the best anthology of the year, but one for the ages.”— The Guardian WINNER OF THE BRAM STOKER AWARD AND THE BRITISH FANTASY AWARD • FINALIST FOR THE WORLD FANTASY AWARD AND THE LOCUS AWARD • A BEST BOOK OF THE YEAR: Esquire, Chicago Public Library, CrimeReads A cop begins seeing huge, blinking eyes where the headlights of cars should be that tell him who to pull over. Two freedom riders take a bus ride that leaves them stranded on a lonely road in Alabama where several unsettling somethings await them. A young girl dives into the depths of the Earth in search of the demon that killed her parents. These are just a few of the worlds of Out There Screaming , Jordan Peele’s anthology of all-new horror stories by Black writers. Featuring an introduction by Peele and an all-star roster of beloved writers and new voices, Out There Screaming is a master class in horror, and—like his spine-chilling films—its stories prey on everything we think we know about our world . . . and redefine what it means to be afraid.   Featuring stories by: Erin E. Adams, Violet Allen, Lesley Nneka Arimah, Maurice Broaddus, Chesya Burke, P. Djèlí Clark, Ezra Claytan Daniels, Tananarive Due, Nalo Hopkinson, N. K. Jemisin, Justin C. Key, L. D. Lewis, Nnedi Okorafor, Tochi Onyebuchi, Rebecca Roanhorse, Nicole D. Sconiers, Rion Amilcar Scott, Terence Taylor, and Cadwell Turnbull.